Heat wave trends in Southeast Asia during 1979–2018: The impact of humidity - Li, Xian-Xiang (The Science of the total environment, 2020)
In tropics, especially Southeast Asia (SEA), heat wave (HW) research is seriously scarce although several global studies have projected this region to be greatly susceptible to increasing HW events under climate change scenarios. Using the recently released ERA5 reanalysis data, we find that in most parts of SEA, HWs are becoming more frequent, longer-lasting and stronger, no matter using dry-bulb or wet-bulb temperatures to define HW. The increasing trends of HW characteristics based on minimum temperatures are larger than those based on maximum temperatures, suggesting an alarming situation of anomalously warm night. HW characteristics based on wet-bulb temperatures show higher increasing rates in the IndoChina Peninsula and Malay Peninsula than those based on dry-bulb temperatures. Nearly all HW characteristics are significantly correlated with El Niño index, but Indian Ocean Dipole only significantly impacts HW characteristics based on wet-bulb temperature in Java. Results derived from other reanalysis products exhibit general agreement with those from ERA5, lending support to the findings reported herein. This study highlights the different role of humidity in changing HW trends in different regions of SEA, and calls for attention to the associated risk of increasing nighttime temperatures during HWs. [Display omitted] •Heat waves are becoming more frequent, longer-lasting and more intense in most Southeast Asia.•HWs based on minimum temperatures increase at higher rate than based on maximum temperatures.•Wet-bulb temperature based HWs show larger increasing trends in Malay and Indochina Peninsulas.•Nearly all HW metrics are significantly correlated with El Nino index, but IOD only impacts Java.•Comparison with different reanalysis datasets demonstrates robustness of our findings.